(10-t)(10+r)=0

Simple and best practice solution for (10-t)(10+r)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (10-t)(10+r)=0 equation:


Simplifying
(10 + -1t)(10 + r) = 0

Multiply (10 + -1t) * (10 + r)
(10(10 + r) + -1t * (10 + r)) = 0
((10 * 10 + r * 10) + -1t * (10 + r)) = 0
((100 + 10r) + -1t * (10 + r)) = 0
(100 + 10r + (10 * -1t + r * -1t)) = 0

Reorder the terms:
(100 + 10r + (-1rt + -10t)) = 0
(100 + 10r + (-1rt + -10t)) = 0
(100 + 10r + -1rt + -10t) = 0

Solving
100 + 10r + -1rt + -10t = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-100' to each side of the equation.
100 + 10r + -1rt + -100 + -10t = 0 + -100

Reorder the terms:
100 + -100 + 10r + -1rt + -10t = 0 + -100

Combine like terms: 100 + -100 = 0
0 + 10r + -1rt + -10t = 0 + -100
10r + -1rt + -10t = 0 + -100

Combine like terms: 0 + -100 = -100
10r + -1rt + -10t = -100

Add '10t' to each side of the equation.
10r + -1rt + -10t + 10t = -100 + 10t

Combine like terms: -10t + 10t = 0
10r + -1rt + 0 = -100 + 10t
10r + -1rt = -100 + 10t

Reorder the terms:
100 + 10r + -1rt + -10t = -100 + 10t + 100 + -10t

Reorder the terms:
100 + 10r + -1rt + -10t = -100 + 100 + 10t + -10t

Combine like terms: -100 + 100 = 0
100 + 10r + -1rt + -10t = 0 + 10t + -10t
100 + 10r + -1rt + -10t = 10t + -10t

Combine like terms: 10t + -10t = 0
100 + 10r + -1rt + -10t = 0

The solution to this equation could not be determined.

See similar equations:

| 8/3c-2=2/3c=12 | | -28m-12=88 | | 0.09xX=61.67 | | P(w)=5w^2-9w+9 | | 3.3q-5.7-3.4q=-2.1q-5.2 | | 7x+(x+20)= | | x-8-12=5 | | (4-s)(4-s)=0 | | 5m^2+28m+32=0 | | x+12-18=26 | | 5m^2+28+32=0 | | -6=-6+0.6y | | 2(x-22)+3=2x-1 | | -6=-6+0.6 | | -24=4x+-12 | | 1+9b-18=-8b+17 | | 5x+1=1.5x+16 | | 3/5r=11 | | 12x+21=4x-25 | | 253+-3y=180 | | -6=2+0.3x | | -2+13j=-15+12j | | 6p^2=64 | | .10x=.4x | | 6s^3-14s^2+4s=2s | | 0.09xX=59.23 | | 21-3q=15 | | x^3+6x^2+-91x-20=0 | | E^2x-3=17 | | 10x+8y=818 | | x^2-4.5x-75=0 | | (b+8)(b+9)=0 |

Equations solver categories